2015
DOI: 10.1186/s12971-015-0029-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole cigarette smoke on human beta defensins expression and secretion by oral mucosal epithelial cells

Abstract: BackgroundCigarette smoke a recognized risk factor for many systemic diseases and also oral diseases. Human beta defensins (HBDs), a group of important antimicrobial peptides expressed by the epithelium, are crucial for local defense and tissue homeostasis of oral cavity. The aim of this study was to evaluate potential effects of whole cigarette smoke (WCS) exposure on the expression and secretion of HBDs by oral mucosal epithelial cells.MethodsImmortalized human oral mucosal epithelial (Leuk-1) cells were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…(37) the expression level of hβD-2 and hβD-3 in GCF among the smoking group was significantly lower than that in the non-smoking group. Also, The mRNA expression level of hβD-2 and hβD-3 in the smoking group was weakened compared with that in the non-smoking group indicating that smoking may have a negative effect on the immune defense system of the periodontal host, however, this study is in agreement with another study by Wang et al (2015) (38) demonstrating that the whole cigarette smoke (WCS) exposure remarkably attenuated hβD-1 expression and secretion while clearly enhanced hβD-2 and hβD-3 expression levels, suggesting a link between cigarette smoke and abnormal levels of antimicrobial peptides.…”
Section: Discussionsupporting
confidence: 91%
“…(37) the expression level of hβD-2 and hβD-3 in GCF among the smoking group was significantly lower than that in the non-smoking group. Also, The mRNA expression level of hβD-2 and hβD-3 in the smoking group was weakened compared with that in the non-smoking group indicating that smoking may have a negative effect on the immune defense system of the periodontal host, however, this study is in agreement with another study by Wang et al (2015) (38) demonstrating that the whole cigarette smoke (WCS) exposure remarkably attenuated hβD-1 expression and secretion while clearly enhanced hβD-2 and hβD-3 expression levels, suggesting a link between cigarette smoke and abnormal levels of antimicrobial peptides.…”
Section: Discussionsupporting
confidence: 91%
“…BDs are important antimicrobial peptides in epithelial innate immunity, and their differential expressions are associated with periodontal disease. 42 Previous studies have demonstrated that healthy gingival tissues present greater expressions of BD-1, BD-2, and BD-3 than tissues of patients with periodontitis. [43][44][45] In the present study, it is possible the exposition of epithelial cells to B. lactis HN019 before induction of periodontitis and during the course of the disease have potentiated the expression of BDs.…”
Section: Discussionmentioning
confidence: 97%
“…A significantly greater expression of BDs was observed in group EP‐HN019 compared with group EP. BDs are important antimicrobial peptides in epithelial innate immunity, and their differential expressions are associated with periodontal disease 42 . Previous studies have demonstrated that healthy gingival tissues present greater expressions of BD‐1, BD‐2, and BD‐3 than tissues of patients with periodontitis 43–45 .…”
Section: Discussionmentioning
confidence: 99%
“…При изучении концентрации β-дефенсина HBD-2 в смывах из ротоглотки и со слизистой бронхов, по-лученных у курящих больных внебольничной пнев-монией, установлено выраженное подавление меха-низмов врожденного иммунитета, которое частично нивелировалось при повышении концентрации пе-рекиси водорода и активности каталазы. Высказа-но предположение, что при курении увеличивается продукция ИЛ-8 и снижается синтез β-дефенсина HBD-2 клетками эпителия ротовой полости [227].…”
Section: патогенетическое значение дефенCинов при инфекционных процессахunclassified